Adhesive tape
By using low molecular weight (meth)acrylic copolymer and crosslinking agent in the adhesive tape, combined with alkali decomposition treatment, the problems of CO2 emission and viscosity increase during the manufacturing process of the adhesive tape are solved, and high-performance and environmentally friendly bonding effect is achieved.
Patent Information
- Application Number
- CN202380057995.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-21
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-07
AI Technical Summary
The existing adhesive tape discharges a large amount of CO2 during the manufacturing process, and the viscosity of the adhesive increases after reducing the solvent amount, affecting processability.
The molecular weight and molecular weight distribution of the copolymer are adjusted by using a binder containing a low molecular weight (meth)acrylic copolymer, a crosslinking agent and a tackifying resin. The molecular weight and molecular weight distribution of the copolymer are adjusted through the crosslinking point base decomposition of the crosslinking product to improve the cohesion and adhesion of the adhesive.
It is achieved while maintaining excellent performance and adhesion, reducing CO2 emissions in the manufacturing process and improving processability.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to adhesive tapes. Background Art
[0002] Adhesive tapes are used for assembly of portable electronic devices such as mobile phones and personal digital assistants (PDAs) (for example, Patent Documents 1 and 2). Adhesive tapes are also used for bonding optical components (for example, Patent Document 3).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2009-242541
[0006] Patent Document 2: Japanese Patent Application Publication No. 2009-258274
[0007] Patent Document 3: Japanese Patent Application Publication No. 2012-214544 Summary of the invention
[0008] Problems to be solved by the invention
[0009] One of the environmental issues that should be considered globally is global warming caused by greenhouse gases. In recent years, the idea of carbon neutrality, where the sum of the amount of greenhouse gas absorbed and removed is zero, has become popular around the world. In the field of electronic devices that use adhesive tapes as components, the trend of creating environmentally friendly products is also accelerating.
[0010] The adhesive used in the formation of the adhesive layer of the adhesive tape usually contains a solvent, so in the manufacturing process of the adhesive tape, CO2 is discharged from the solvent. By reducing the amount of solvent contained in the adhesive, the CO2 discharged in the manufacturing process can be reduced, but if the amount of solvent is only reduced, there is a problem of increased viscosity and reduced processability of the adhesive. In order to prevent the viscosity from increasing even if the amount of solvent is reduced, that is, even if the proportion of solid components in the adhesive is increased, it is necessary to reduce the molecular weight of components such as (meth) acrylic copolymers contained in the adhesive. On the other hand, as the functions required for the adhesive layer, the retention performance including the cohesion and heat resistance of the body (Japanese: バルク) and the adhesion including the wettability of the interface and the fluidity of the body can be cited. In order to meet these properties, components such as (meth) acrylic copolymers used in conventional adhesives need to have a molecular weight of about 500,000 or more.
[0011] An object of the present invention is to provide a pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer that uses a (meth)acrylic copolymer having a low molecular weight and has excellent holding performance and adhesiveness.
[0012] Means for solving problems
[0013] The present invention 1 relates to an adhesive tape, comprising an adhesive layer, wherein the adhesive layer contains a cross-linked product of an adhesive, wherein the adhesive comprises a (meth)acrylic acid copolymer, a cross-linking agent and a tackifying resin, wherein when a (meth)acrylic acid copolymer obtained by alkali decomposition of the cross-linking points of the cross-linked product is subjected to GPC measurement based on RI detection of a differential refractometer, the weight average molecular weight of the (meth)acrylic acid copolymer in the region of molecular weight of 5,000 or more is 80,000 or more and less than 500,000, and in a holding test in which a load of 1 kg is applied to the adhesive tape bonded to a SUS plate in a shear direction for 24 hours at 80°C, the adhesive tape does not fall off, and the 180° peeling adhesion of the adhesive tape to the SUS plate is 15 N / 25 mm or more.
[0014] The present invention 2 relates to an adhesive tape comprising an adhesive layer, wherein the adhesive layer contains a cross-linked product of an adhesive, wherein the adhesive comprises a (meth)acrylic acid copolymer, a cross-linking agent and a tackifier resin, wherein when a (meth)acrylic acid copolymer obtained by alkali decomposition of the cross-linking points of the cross-linked product is subjected to GPC measurement based on RI detection of a differential refractometer, the weight average molecular weight of the (meth)acrylic acid copolymer in the region of molecular weight of 5,000 or more is 80,000 or more and less than 500,000, and the adhesive layer satisfies the following first constitution, the following second constitution or the following third constitution.
[0015] A first configuration: the adhesive contains 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the adhesive layer has a gel fraction of 5% by mass or more;
[0016] A second configuration: the adhesive contains 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, the adhesive layer has a gel fraction of less than 5% by mass, and a value obtained by subtracting a weight average molecular weight of the (meth)acrylic copolymer in a molecular weight range of 5,000 or more when subjected to GPC measurement using a differential refractometer RI detection of the sol component of the adhesive layer from a weight average molecular weight of the sol component in a molecular weight range of 5,000 or more when subjected to GPC measurement using a differential refractometer RI detection of the (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is 80,000 or more;
[0017] A third configuration: the pressure-sensitive adhesive contains 0.1 parts by mass or more and less than 6 parts by mass of the cross-linking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction exceeding 30% by mass.
[0018] The third aspect of the present invention relates to the pressure-sensitive adhesive tape of the second aspect of the present invention, wherein the pressure-sensitive adhesive layer satisfies the first configuration.
[0019] The present invention 4 is related with the adhesive tape of the present invention 2, wherein the adhesive layer satisfies the second configuration.
[0020] The fifth aspect of the present invention is the pressure-sensitive adhesive tape according to the second aspect of the present invention, wherein the pressure-sensitive adhesive layer satisfies the third configuration.
[0021] The present invention 6 relates to the pressure-sensitive adhesive tape according to the present invention 1, wherein the pressure-sensitive adhesive layer satisfies the following first configuration, the following second configuration, or the following third configuration.
[0022] A first configuration: the adhesive contains 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the adhesive layer has a gel fraction of 5% by mass or more;
[0023] A second configuration: the adhesive contains 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, the adhesive layer has a gel fraction of less than 5% by mass, and a value obtained by subtracting a weight average molecular weight of the (meth)acrylic copolymer in a molecular weight range of 5,000 or more when subjected to GPC measurement using a differential refractometer RI detection of the sol component of the adhesive layer from a weight average molecular weight of the sol component in a molecular weight range of 5,000 or more when subjected to GPC measurement using a differential refractometer RI detection of the (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is 80,000 or more;
[0024] A third configuration: the pressure-sensitive adhesive contains 0.1 parts by mass or more and less than 6 parts by mass of the cross-linking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction exceeding 30% by mass.
[0025] Invention 7 relates to the adhesive tape of invention 2 or 6, wherein the adhesive layer has the following structure as the above-mentioned first structure: the above-mentioned adhesive contains 6 parts by mass or more of the above-mentioned cross-linking agent relative to 100 parts by mass of the above-mentioned (meth)acrylic copolymer, and the gel fraction of the above-mentioned adhesive layer is 5% by mass or more and less than 30% by mass; or, the above-mentioned adhesive layer has the following structure as the above-mentioned third structure: the above-mentioned adhesive contains 1.5 parts by mass or more and less than 6 parts by mass of the above-mentioned cross-linking agent relative to 100 parts by mass of the above-mentioned (meth)acrylic copolymer, and the gel fraction of the above-mentioned adhesive layer exceeds 30% by mass.
[0026] Invention 8 relates to the adhesive tape of invention 7, wherein the adhesive layer has the following structure as the first structure: the adhesive contains 6 parts by mass or more of the cross-linking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the adhesive layer is 5% by mass or more and less than 30% by mass.
[0027] Invention 9 relates to the adhesive tape of invention 7, wherein the adhesive layer has the following structure as the third structure: the adhesive contains 1.5 parts by mass or more and less than 6 parts by mass of the cross-linking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the adhesive layer exceeds 30% by mass.
[0028] Invention 10 relates to the adhesive tape of invention 1, 2, 3, 4, 5, 6, 7, 8 or 9, wherein, when the sol component of the above-mentioned adhesive layer is subjected to GPC measurement based on differential refractometer RI detection, the weight average molecular weight of the sol component in the region of molecular weight above 5000 is 50,000 or more and 500,000 or less.
[0029] Invention 11 relates to the pressure-sensitive adhesive tape of invention 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, wherein when a (meth)acrylic acid-based copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is subjected to GPC measurement using a differential refractometer RI detection, the peak top molecular weight of the (meth)acrylic acid-based copolymer in the region of molecular weight of 5,000 or more is 70,000 or more and 300,000 or less.
[0030] Invention 12 relates to the adhesive tape of invention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or 11, wherein the adhesive contains 0.03 mass % or more of a compound having a hydroxyl group in the solid content and 2 mass % or more of a compound having a carboxyl group in the solid content.
[0031] Invention 13 relates to the pressure-sensitive adhesive tape of invention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, wherein the (meth)acrylic copolymer has 50% by mass or more of a structural unit derived from a monomer having an alkyl group having 6 or more carbon atoms.
[0032] Invention 14 relates to the pressure-sensitive adhesive tape according to invention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, wherein the pressure-sensitive adhesive layer has a glass transition temperature of -10°C or higher and 30°C or lower.
[0033] Invention 15 relates to the adhesive tape of invention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14, wherein the storage modulus G' (80°C) of the adhesive layer at 80°C is 1.0×10 4 Pa or above.
[0034] Invention 16 relates to the pressure-sensitive adhesive tape of invention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, wherein the thickness of the pressure-sensitive adhesive layer is 10 μm or more and 100 μm or less.
[0035] Invention 17 relates to the adhesive tape of invention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16, wherein the adhesive tape has a substrate, the substrate is a polyester resin film or a polypropylene resin film, and the thickness of the substrate is greater than or equal to 5 μm and less than or equal to 200 μm.
[0036] Invention 18 relates to the adhesive tape of invention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17, wherein the adhesive tape has a substrate and has the adhesive layer on both sides of the substrate.
[0037] Hereinafter, the present invention will be described in detail.
[0038] It should be noted that the adhesive tape of the first embodiment of the present invention is also referred to as the "adhesive tape of the first embodiment of the present invention", and the adhesive tape of the second embodiment of the present invention is also referred to as the "adhesive tape of the second embodiment of the present invention". In addition, matters common to the adhesive tape of the first embodiment of the present invention and the adhesive tape of the second embodiment are not particularly specified or described as the "adhesive tape of the present invention".
[0039] The present inventors have found that even when a pressure-sensitive adhesive layer containing a (meth)acrylic copolymer having a specific low molecular weight is used to form the pressure-sensitive adhesive layer, a pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer excellent in holding performance and adhesiveness can be obtained by providing the pressure-sensitive adhesive layer with a specific structure, thereby completing the present invention.
[0040] The pressure-sensitive adhesive tape of the present invention is a pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer.
[0041] The pressure-sensitive adhesive layer contains a cross-linked product of a pressure-sensitive adhesive including a (meth)acrylic copolymer, a cross-linking agent, and a tackifying resin.
[0042] In addition, in this specification, "(meth)acrylic acid" means acrylic acid or methacrylic acid.
[0043] In the pressure-sensitive adhesive tape of the present invention, when the pressure-sensitive adhesive layer is subjected to GPC measurement using a differential refractometer RI detection on a (meth)acrylic acid-based copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product, the weight average molecular weight of the (meth)acrylic acid-based copolymer in the region of molecular weight of 5,000 or more (hereinafter also referred to as "the weight average molecular weight of the (meth)acrylic acid-based copolymer obtained by alkali decomposition") is 80,000 or more and less than 500,000.
[0044] By making the weight average molecular weight of the (meth)acrylic acid copolymer obtained by alkali decomposition to be 80,000 or more, the cohesive force of the main body in the obtained adhesive layer becomes large, and the heat resistance of the adhesive layer becomes excellent. By making the weight average molecular weight of the (meth)acrylic acid copolymer obtained by alkali decomposition to be less than 500,000, the viscosity of the adhesive used to form the above-mentioned adhesive layer can be reduced, the processability can be improved, and the amount of the solvent that becomes the source of CO2 discharged in the manufacturing process can be reduced. The preferred lower limit of the weight average molecular weight of the (meth)acrylic acid copolymer obtained by alkali decomposition is 100,000, the more preferred lower limit is 150,000, the preferred upper limit is 490,000, the more preferred upper limit is 450,000, and the more preferred upper limit is 400,000.
[0045] It should be noted that, in the present specification, the "(meth)acrylic acid copolymer obtained by alkali decomposition" may be the (meth)acrylic acid copolymer contained in the above-mentioned adhesive, or may be other compounds. Examples of other compounds include: (meth)acrylic acid copolymers in which a part of the structure of the (meth)acrylic acid copolymer contained in the above-mentioned adhesive is modified and / or missing.
[0046] In addition, the alkali decomposition of the crosslinking points of the crosslinked product was performed by the following method.
[0047] Specifically, 300 mg of the adhesive layer, 6 mL of ethanol, and 7 mL of a 60% KOH aqueous solution were placed in a pressure vessel and hydrolyzed under pressure in an oven at 160° C. for 60 hours to alkali decompose the crosslinking points of the crosslinked product to obtain a (meth)acrylic copolymer.
[0048] When the (meth)acrylic acid-based copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is subjected to GPC measurement using a differential refractometer RI detection, for example, the following method can be employed.
[0049] Specifically, the (meth)acrylic acid-based copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is analyzed by gel permeation chromatography (GPC) (manufactured by Waters, "2690 Separations Model") to measure the molecular weight distribution based on polystyrene conversion. The GPC can be performed under the following conditions.
[0050] Eluent: Tetrahydrofuran (THF)
[0051] Flow rate: 0.4mL / min
[0052] Detector: Differential Refractometer RI
[0053] Column: LF-804 (manufactured by SHOKO)
[0054] Column temperature (measurement temperature): 40°C
[0055] Injection volume: 20 μL
[0056] In the pressure-sensitive adhesive tape of the present invention, when the pressure-sensitive adhesive layer is subjected to GPC measurement using a differential refractometer RI detection on a (meth)acrylic acid-based copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product, the peak top molecular weight of the (meth)acrylic acid-based copolymer in the region of molecular weight of 5,000 or more (hereinafter also referred to as “the peak top molecular weight of the (meth)acrylic acid-based copolymer obtained by alkali decomposition”) is preferably 70,000 and the upper limit is preferably 300,000.
[0057] By setting the peak top molecular weight of the (meth)acrylic acid copolymer obtained by alkali decomposition to 70,000 or more, the cohesive force of the main body in the obtained adhesive layer becomes larger, and the heat resistance of the adhesive layer becomes more excellent. By setting the peak top molecular weight of the (meth)acrylic acid copolymer obtained by alkali decomposition to 300,000 or less, the viscosity of the adhesive used to form the adhesive layer can be further reduced, the processability can be further improved, and the amount of the solvent that becomes the source of CO2 discharged in the manufacturing process can be further reduced. The more preferred lower limit of the peak top molecular weight of the (meth)acrylic acid copolymer obtained by alkali decomposition is 80,000, the more preferred lower limit is 100,000, the more preferred upper limit is 250,000, and the more preferred upper limit is 230,000.
[0058] It should be noted that, in this specification, "peak molecular weight" refers to the molecular weight at the highest peak in the molecular weight distribution curve. Even if there is a shoulder peak or two or more peaks in the molecular weight distribution curve, the peak molecular weight refers to the molecular weight at the highest peak in the molecular weight distribution curve.
[0059] In the pressure-sensitive adhesive tape of the present invention, for the pressure-sensitive adhesive layer, when a (meth)acrylic acid-based copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is subjected to GPC measurement based on RI detection of a differential refractometer, the polydispersity coefficient of the (meth)acrylic acid-based copolymer in the region of molecular weight of 5,000 or more (hereinafter also referred to as "polydispersity coefficient of the (meth)acrylic acid-based copolymer obtained by alkali decomposition") is preferably 15,000 in the lower limit, 100,000 in the upper limit, and more preferably 60,000 in the upper limit, from the viewpoint of adjusting the molecular weight distribution.
[0060] It should be noted that the polydispersity coefficient refers to the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn).
[0061] In the adhesive tape of the present invention, for the above-mentioned adhesive layer, when the sol component of the above-mentioned adhesive layer is subjected to GPC measurement based on differential refractometer RI detection, the preferred lower limit of the weight average molecular weight of the sol component in the region of molecular weight above 5000 (hereinafter, also referred to as "the weight average molecular weight of the sol component") is 50,000, and the preferred upper limit is 500,000. By making the weight average molecular weight of the above-mentioned sol component above 50,000, the cohesive force of the main body in the obtained adhesive layer becomes greater, and the heat resistance and high temperature rebound resistance (Japanese: high temperature rebound resistance) of the adhesive layer become more excellent. By making the weight average molecular weight of the above-mentioned sol component below 500,000, the viscosity of the adhesive used to form the above-mentioned adhesive layer can be further reduced, the processability can be further improved, and the amount of solvent that becomes the source of CO2 discharged in the manufacturing process can be further reduced. The more preferred lower limit of the weight average molecular weight of the above-mentioned sol component is 70,000, the more preferred lower limit is 100,000, the more preferred upper limit is 400,000, and the more preferred upper limit is 300,000.
[0062] Here, the "sol component" refers to the component after the "gel component" is removed from the adhesive layer. It should be noted that the "gel component" is a component with low fluidity remaining on the mesh in the gel fraction measurement process in which the (meth)acrylic copolymer, the tackifying resin described later, etc. have a cross-linked structure with the help of the cross-linking agent described later, and the "sol component" is a component with high fluidity after the gel component is removed in the above process.
[0063] The sol component of the adhesive layer can be obtained by, for example, immersing the adhesive layer in tetrahydrofuran (THF) at 23° C. for 24 hours, filtering the insoluble components with a 200-mesh metal mesh, and removing the gel component.
[0064] When the sol component of the pressure-sensitive adhesive layer is subjected to GPC measurement using RI detection with a differential refractometer, for example, the following method can be employed.
[0065] Specifically, the sol component of the pressure-sensitive adhesive layer is analyzed by gel permeation chromatography (GPC) (manufactured by Waters, “2690 Separations Model”) to measure the molecular weight distribution based on polystyrene conversion. The GPC can be performed under the following conditions.
[0066] Eluent: Tetrahydrofuran (THF)
[0067] Flow rate: 0.4mL / min
[0068] Detector: Differential Refractometer RI
[0069] Column: LF-804 (manufactured by SHOKO)
[0070] Column temperature (measurement temperature): 40°C
[0071] Injection volume: 20 μL
[0072] In the adhesive tape of the present invention, for the above-mentioned adhesive layer, when the sol component of the above-mentioned adhesive layer is subjected to GPC measurement based on differential refractometer RI detection, the peak top molecular weight of the sol component in the region of molecular weight above 5000 (hereinafter, also referred to as "the peak top molecular weight of the sol component") is preferably 30,000 and the upper limit is 300,000. By making the peak top molecular weight of the above-mentioned sol component above 30,000, the cohesive force of the main body in the obtained adhesive layer becomes greater, and the heat resistance of the adhesive layer becomes more excellent. By making the peak top molecular weight of the above-mentioned sol component below 300,000, the viscosity of the adhesive used to form the above-mentioned adhesive layer can be further reduced, the processability can be further improved, and the amount of the solvent that becomes the source of CO2 discharged in the manufacturing process can be further reduced. The more preferred lower limit of the peak top molecular weight of the above-mentioned sol component is 70,000, the further preferred lower limit is 80,000, the more preferred upper limit is 250,000, and the further preferred upper limit is 230,000.
[0073] Regarding the adhesive tape of the present invention 1, after being adhered to the SUS plate and subjected to a holding test at 80°C with a 1 kg load applied in the shear direction for 24 hours, the adhesive tape does not fall off. The heat resistance of the adhesive tape showing the results of the above holding test becomes excellent. For example, the fixing of components used in electronic devices becomes good. As a result of the above holding test, it is preferably free of offsets of 1 mm or more, and more preferably free of offsets of 0.5 mm or more.
[0074] In addition, regarding the adhesive tape of the present invention 2, after being adhered to the SUS plate and subjected to a holding test at 80°C with a 1 kg load applied in the shear direction for 24 hours, it is preferably that the adhesive tape does not fall off. The heat resistance of the adhesive tape showing the results of the above holding test becomes more excellent. For example, the fixing of components used in electronic devices becomes better. As a result of the above holding test, it is more preferably free of offsets of 1 mm or more, and further preferably free of offsets of 0.5 mm or more.
[0075] The above holding test can be carried out by the following method. In addition, a schematic diagram showing the method of the above holding test is shown in Figure 1 .
[0076] That is, first, the adhesive tape 1 is cut into a long strip with a width of 25 mm and then adhered to the SUS plate 2 by reciprocating a 2 kg rubber roller at a speed of 300 mm / min once. Next, a dent is introduced into the adhesive tape 1 so that the bonding area becomes 25 mm × 25 mm. Then, after standing at 23°C for 20 minutes, it is placed in an oven at 80°C, further heated for 15 minutes, and while maintaining at 80°C, as Figure 1 shown, a 1 kg load is applied in the shear direction using a 1 kg weight 3. Check whether the adhesive tape falls off, and when it does not fall off after 24 hours, measure the amount of movement (offset) from the dent position using a scale magnifier.
[0077] Regarding the adhesive tape of the present invention 1, the 180° peel adhesion force (Japanese: 引きはがし粘着力) of the adhesive tape to the SUS plate is 15 N / 25 mm or more. Specifically, after being adhered to the SUS plate, the 180° peel adhesion force in a 180° direction tensile test conducted under the conditions of 23°C and a peel speed of 300 mm / min in accordance with JIS Z0237 is 15 N / 25 mm or more. By making the above 180° peel adhesion force 15 N / 25 mm or more, the adhesive tape can have sufficient adhesiveness. For example, the fixing of components used in electronic devices becomes good. The above 180° peel adhesion force is preferably 18 N / 25 mm or more, and more preferably 20 N / 25 mm or more.
[0078] In addition, regarding the adhesive tape of the present invention 2, it is preferred that the 180° peeling adhesion of the adhesive tape to the SUS plate is 15N / 25mm or more. Specifically, after being bonded to the SUS plate, the 180° peeling adhesion during a tensile test in a 180° direction at 23°C and a peeling speed of 300mm / min according to JIS Z0237 is preferably 15N / 25mm or more. By making the above-mentioned 180° peeling adhesion be 15N / 25mm or more, the adhesive tape can have sufficient adhesion, for example, the fixation of components used in electronic devices becomes good. The above-mentioned 180° peeling adhesion is more preferably 18N / 25mm or more, and further preferably 20N / 25mm or more.
[0079] The 180° peel strength can be measured by the following method.
[0080] That is, first, after the adhesive tape is cut into a strip with a width of 25 mm, it is bonded to the SUS plate by reciprocating a 2 kg rubber roller once at a speed of 300 mm / min. Next, it is left to stand for 20 minutes at a temperature of 23° C. and a relative humidity of 50%, thereby obtaining a test piece. For the obtained test piece, a tensile test is performed using a tensile testing machine according to JIS Z0237 at 23° C., a peeling speed of 300 mm / min, and a peeling angle of 180°, thereby measuring the above-mentioned 180° peeling adhesive force.
[0081] In the adhesive tape of the second aspect, the adhesive layer satisfies the first constitution, the second constitution, or the third constitution described below. In the adhesive tape of the first aspect, the adhesive layer preferably satisfies the first constitution, the second constitution, or the third constitution described below.
[0082] A first configuration: the adhesive contains 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the adhesive layer has a gel fraction of 5% by mass or more;
[0083] A second configuration: the adhesive contains 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, the adhesive layer has a gel fraction of less than 5% by mass, and a value obtained by subtracting a weight average molecular weight of the (meth)acrylic copolymer in a molecular weight range of 5,000 or more when subjected to GPC measurement using a differential refractometer RI detection of the sol component of the adhesive layer from a weight average molecular weight of the sol component in a molecular weight range of 5,000 or more when subjected to GPC measurement using a differential refractometer RI detection of the (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is 80,000 or more;
[0084] A third configuration: the pressure-sensitive adhesive contains 0.1 parts by mass or more and less than 6 parts by mass of the cross-linking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction exceeding 30% by mass.
[0085] In the adhesive tape of the second aspect of the present invention, the adhesive layer satisfies the first constitution, the second constitution, or the third constitution, so that the holding performance and adhesiveness of the obtained adhesive layer become excellent. In addition, in the adhesive tape of the first aspect of the present invention, the adhesive layer satisfies the first constitution, the second constitution, or the third constitution, so that the holding performance and adhesiveness of the obtained adhesive layer become even better.
[0086] In the first configuration, if the adhesive has 6 parts by mass or more of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the adhesive layer is 5% by mass or more, the cohesive force of the main body in the obtained adhesive layer becomes large, and the heat resistance of the adhesive layer becomes excellent. This is because even if the molecular weight of the (meth)acrylic copolymer is small and the gel fraction is low, if the crosslinking agent is present in a large amount, it is considered that crosslinking and high molecular weight in the sol component are promoted. In the first configuration, the gel fraction of the adhesive layer is preferably 10% by mass or more, and more preferably 15% by mass or more.
[0087] In addition, the gel fraction of the said pressure-sensitive adhesive layer in the said first structure, the said second structure, and the said third structure can be measured by the following method, for example.
[0088] That is, first, W1 (g) of the adhesive layer is collected, and the collected adhesive layer is immersed in ethyl acetate at 23°C for 24 hours, and the insoluble components are filtered with a 200-mesh metal mesh. The residue on the metal mesh is heated and dried at 110°C, and the mass W2 (g) of the obtained dry residue is measured. From the obtained W1 and W2, the gel fraction (crosslinking degree) is calculated by the following formula (I).
[0089] Gel fraction (mass %) = 100 × W2 / W1 (I)
[0090] In the first configuration, the gel fraction of the adhesive layer is preferably less than 30% by mass. In the first configuration, by making the gel fraction of the adhesive layer less than 30% by mass, the decrease in the fluidity of the body caused by the increase in the elastic modulus of the adhesive layer is suppressed, and the adhesive layer does not significantly reduce the wettability of the interface, and the adhesiveness becomes more excellent. In the first configuration, the gel fraction of the adhesive layer is more preferably less than 28% by mass.
[0091] In the first configuration, the content of the crosslinking agent in the adhesive is preferably 12 parts by mass or less relative to 100 parts by mass of the (meth)acrylic copolymer. In the first configuration, by making the content of the crosslinking agent in the adhesive 12 parts by mass or less, the decrease in the fluidity of the body caused by the increase in the elastic modulus of the adhesive layer is suppressed, and the adhesive layer does not significantly reduce the wettability of the interface, and the adhesiveness becomes more excellent. In the first configuration, the content of the crosslinking agent in the adhesive is more preferably 10 parts by mass or less.
[0092] In the second configuration, the value obtained by subtracting the weight average molecular weight of the (meth) acrylic copolymer obtained by alkali decomposition from the weight average molecular weight of the sol component in the region of molecular weight 5000 or more when the sol component of the adhesive layer is measured by GPC based on differential refractometer RI detection is 80,000 or more. Thus, even if the gel fraction of the adhesive layer is small, crosslinking of the polymer in the sol component will proceed, the molecular weight will increase, and the cohesive force of the main body in the adhesive layer will be high. In the second configuration, the preferred lower limit of the gel fraction of the adhesive layer is 0.1% by mass, and the more preferred lower limit is 1% by mass. In addition, in the second configuration, the preferred lower limit of the value obtained by subtracting the weight average molecular weight of the (meth) acrylic copolymer obtained by alkali decomposition from the weight average molecular weight of the sol component is 100,000, and the more preferred lower limit is 120,000.
[0093] In the third configuration, by making the gel fraction of the adhesive layer exceed 30% by mass, the cohesive force of the main body in the adhesive layer becomes large, and the heat resistance of the adhesive layer becomes excellent. In the third configuration, the gel fraction of the adhesive layer is preferably 31% by mass or more, more preferably 35% by mass or more, further preferably 40% by mass or more, and further preferably 45% by mass or more.
[0094] In addition, in the third configuration, the gel fraction of the adhesive layer is preferably 70% by mass or less. In the third configuration, by making the gel fraction of the adhesive layer 70% by mass or less, the decrease in the fluidity of the body in the adhesive layer is suppressed, and the adhesive layer does not significantly reduce the wettability of the interface, and the adhesion becomes more excellent. In the third configuration, the gel fraction of the adhesive layer is more preferably 65% by mass or less, and further preferably 60% by mass or less.
[0095] In addition, in the third configuration, the content of the crosslinking agent in the adhesive is preferably 0.1 parts by mass or more relative to 100 parts by mass of the (meth)acrylic copolymer. In the third configuration, by making the content of the crosslinking agent in the adhesive 0.1 parts by mass or more, the gel fraction of the adhesive layer obtained is easily increased, and the cohesive force of the body becomes larger. In the third configuration, the content of the crosslinking agent in the adhesive is more preferably 1.5 parts by mass or more, and further preferably 2 parts by mass or more.
[0096] Preferably, the adhesive layer has the following structure as the first structure: the adhesive contains 6 parts by mass or more of the cross-linking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the adhesive layer is 5% by mass or more and less than 30% by mass; or, the adhesive layer has the following structure as the third structure: the adhesive contains 1.5 parts by mass or more and less than 6 parts by mass of the cross-linking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the adhesive layer exceeds 30% by mass.
[0097] Regarding the above-mentioned adhesive layer, the weight average molecular weight, peak molecular weight and polydispersity coefficient of the (meth) acrylic copolymer obtained by alkali decomposition, the weight average molecular weight and peak molecular weight of the above-mentioned sol component, and the value obtained by subtracting the weight average molecular weight of the (meth) acrylic copolymer obtained by alkali decomposition from the weight average molecular weight of the above-mentioned sol component to adjust to the above-mentioned range are not particularly limited. Specifically, for example, a method of using a (meth) acrylic copolymer obtained by polymerization methods such as active free radical polymerization and free radical polymerization as the (meth) acrylic copolymer contained in the above-mentioned adhesive. Among them, from the viewpoint of shortening the reaction time and suppressing the cost, it is preferred to use a method of (meth) acrylic copolymer obtained by free radical polymerization. In addition, from the viewpoint of uniformly introducing crosslinking points, active free radical polymerization is preferred. If the crosslinking points are uniformly introduced, the obtained adhesive layer becomes a uniform crosslinking structure, the cohesive force of the body becomes larger, and the creep resistance is improved. On the other hand, if the cohesive force of the body becomes too large, the flexibility of the adhesive layer is impaired, and the adhesion to the interface is reduced.
[0098] Furthermore, by controlling the weight average molecular weight of the (meth)acrylic acid-based copolymer obtained by the above-mentioned polymerization method, the weight average molecular weight and peak top molecular weight of the (meth)acrylic acid-based copolymer obtained by the above-mentioned alkali decomposition can be adjusted.
[0099] Among the (meth)acrylic acid copolymers obtained by the above-mentioned polymerization method, it is preferable to use a (meth)acrylic acid copolymer obtained by keeping the polymerization temperature and the concentration of the monomer mixture fixed under relatively stable polymerization conditions. In this way, the composition of the above-mentioned (meth)acrylic acid copolymer can be made more uniform, or the polydispersity coefficient of the above-mentioned (meth)acrylic acid copolymer obtained by alkali decomposition can be reduced, and the molecular weight distribution of the sol component of the above-mentioned adhesive layer can be easily adjusted. As a polymerization method that achieves such relatively stable polymerization conditions, for example, there can be mentioned: a method of performing free radical constant temperature polymerization; a method of adding half of the monomer mixture and a polymerization initiator into a reactor in free radical boiling point polymerization to initiate polymerization, and then adding the remaining half of the monomer mixture dropwise or all at once; etc.
[0100] In the above-mentioned polymerization method, it is preferred to react in 2 to 10 hours. If the polymerization time is not properly adjusted, then in free radical polymerization, since the reaction rate of the monomer containing the crosslinking functional group is fast, the introduction of the crosslinking points of the polymer chain becomes uneven, or the residual monomer amount remains much, and the creep resistance decreases.
[0101] The preferred lower limit of the polymerization reaction time in the above-mentioned polymerization method is 2 hours, and the preferred upper limit is 10 hours. By setting the above-mentioned polymerization reaction time in this range, it is easy to adjust the weight average molecular weight of the (meth)acrylic acid copolymer obtained by the above-mentioned alkali decomposition to the above-mentioned range. The more preferred lower limit of the above-mentioned polymerization reaction time is 3 hours, and the more preferred upper limit is 8 hours.
[0102] Examples of the polymerization initiator used in the above-mentioned polymerization method include azo compounds and organic peroxides.
[0103] Examples of the azo compound include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1-azobis(cyclohexane-1-carbonitrile), 1-((1-cyano-1-methylethyl)azo)formamide, 4,4'-azobis(4-cyanovaleric acid), dimethyl-2,2'-azobis(2-methylpropionate), dimethyl-1,1'-azobis(1-cyclohexanecarboxylate), 2,2'-azobis(2-methyl-N-(1,1'-bis(hydroxymethyl)-2-hydroxyethyl)propionamide), 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide). Bis(N-(2-propenyl)-2-methylpropionamide), 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide), 2,2'-azobis(2-(2-imidazolin-2-yl)propane) dihydrochloride, 2,2'-azobis(2-(1-(2-hydroxyethyl)-2-imidazolin-2-yl)propane) dihydrochloride salt, 2,2'-azobis(2-(2-imidazolin-2-yl)propane), 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N-(2-carboxyethyl)-2-methylpropionamidine) tetrahydrate, 2,2'-azobis(1-imino-1-pyrrolidinyl-2-methylpropane) dihydrochloride, 2,2'-azobis(2,4,4-trimethylpentane), etc. These azo compounds may be used alone or in combination of two or more.
[0104] Examples of the organic peroxide include 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, etc. These organic peroxides may be used alone or in combination of two or more.
[0105] Among the above-mentioned polymerization initiators, polymerization initiators having a functional group are preferred.
[0106] By using the above-mentioned polymerization initiator having a functional group, a functional group can be introduced into the terminal of the above-mentioned (meth) acrylic copolymer. In particular, in the above-mentioned (meth) acrylic copolymer, a functional group can also be introduced into the terminal of a molecular chain with a small molecular weight that lacks a structural unit from a monomer containing a crosslinking functional group. Such a low molecular weight chain is introduced into the crosslinking structure with the help of a crosslinking agent described later by having a functional group at the terminal, so that the cohesive force of the main body in the obtained adhesive layer becomes greater, and the heat resistance of the adhesive layer becomes more excellent. In addition, even if it does not participate in the crosslinking structure, with respect to the above-mentioned low molecular weight chain, by having a functional group at the terminal, with the help of a crosslinking agent described later, or with the help of a combination of a crosslinking agent described later and a tackifying resin described later, the low molecular weight chains can form a combination (such as a dimer, etc.) with each other. In such a case, it can be said that the (meth) acrylic copolymer contained in the sol component of the above-mentioned adhesive layer has been subjected to high molecular weight as a whole. Therefore, it is easy to adjust the weight average molecular weight of the sol component to the above range, and the cohesive force of the bulk of the obtained adhesive layer becomes larger, and the heat resistance of the adhesive layer becomes more excellent.
[0107] As the functional group, for example, a hydroxyl group, a carboxyl group, a silyl group, a glycidyl group, an amino group, an amide group, a nitrile group, an alkoxy group, an acetoacetyl group, etc. can be cited. Among them, a hydroxyl group and a carboxyl group are preferred. As the polymerization initiator having a functional group, among the polymerization initiators, for example, 2,2'-azobis(2-methyl-N-(1,1'-bis(hydroxymethyl)-2-hydroxyethyl)propionamide), 4,4'-azobis(4-cyanovaleric acid (valeric acid)) and the like can be cited. These polymerization initiators having functional groups can be used alone or in combination of two or more.
[0108] Relative to 100 parts by mass of the monomer mixture, the preferred lower limit of the addition of the above-mentioned polymerization initiator is 0.01 parts by mass, and the preferred upper limit is 0.5 parts by mass. By making the above-mentioned polymerization initiator within this range, the weight average molecular weight of the above-mentioned sol component can be easily adjusted to the above range. The more preferred lower limit of the addition of the above-mentioned polymerization initiator is 0.02 parts by mass, and the more preferred upper limit is 0.3 parts by mass.
[0109] In the above-mentioned radical polymerization, a chain transfer agent may be used.
[0110] Examples of the chain transfer agent include: dodecyl mercaptan, mercaptopropionic acid, mercaptosuccinic acid, 3-mercapto-1,2-propylene glycol, 1-butyl mercaptan, 3-mercaptopropionic acid cyclohexyl ester, 2-ethylhexyl thioglycolate, 1-hexadecyl mercaptan, 2-mercaptoethanol, thioglycolic acid, ethyl thioglycolate, 1-octyl mercaptan, 3-mercaptopropionic acid tridecyl ester, thiophenol and other thiol compounds. In addition, 2,4-diphenyl-4-methyl-1-pentene and the like can also be mentioned. These chain transfer agents can be used alone or in combination of two or more.
[0111] Among the above chain transfer agents, it is preferred to use a chain transfer agent having a functional group.
[0112] By using the chain transfer agent having a functional group, it is also easy to adjust the weight average molecular weight and the like of the sol component to the above range.
[0113] That is, by using the above-mentioned chain transfer agent having a functional group, it is possible to introduce a functional group into the end of the above-mentioned low molecular weight chain in the same manner as when using the above-mentioned polymerization initiator having a functional group. As a result, the cohesive force of the main body in the obtained adhesive layer becomes greater and the creep resistance of the adhesive layer becomes better.
[0114] As the functional group, for example, hydroxyl, carboxyl, silyl, glycidyl, amino, amide, nitrile, alkoxy, acetoacetyl, etc. can be cited. Among them, hydroxyl and carboxyl are preferred, and hydroxyl is more preferred. In particular, in a system where carboxyl groups are concentrated in high molecular weight polymer chains, a hydroxyl group can be added to the end of a low molecular weight chain by using a chain transfer agent having a hydroxyl group as a functional group, thereby enabling a cross-linking reaction of the low molecular weight chain to be performed advantageously.
[0115] From the perspective that the cross-linked structure is easy to be high-dimensional, easy to be networked, and the cohesive force of the main body in the above-mentioned adhesive layer becomes greater, the number of functional groups of the above-mentioned chain transfer agent with functional groups is preferably multivalent. As the above-mentioned chain transfer agent with functional groups, among the above-mentioned chain transfer agents, for example, mercaptopropionic acid, mercaptosuccinic acid, 3-mercapto-1,2-propylene glycol, etc. can be cited. These chain transfer agents with functional groups can be used alone or in combination of two or more.
[0116] The preferred lower limit of the amount of the chain transfer agent added is 0.01 parts by mass, and the preferred upper limit is 0.5 parts by mass, relative to 100 parts by mass of the monomer mixture. By making the amount of the chain transfer agent added within this range, it is easy to adjust the weight average molecular weight of the sol component to the above range. The more preferred lower limit of the amount of the chain transfer agent added is 0.02 parts by mass, and the more preferred upper limit is 0.3 parts by mass.
[0117] In the above-mentioned radical polymerization, a dispersion stabilizer may be used.
[0118] Examples of the dispersion stabilizer include polyvinyl pyrrolidone, polyvinyl alcohol, methyl cellulose, ethyl cellulose, poly(meth)acrylic acid, poly(meth)acrylate, polyethylene glycol, etc. These dispersion stabilizers may be used alone or in combination of two or more.
[0119] When a polymerization solvent is used in the above-mentioned free radical polymerization, as the polymerization solvent, for example, non-polar solvents such as hexane, cyclohexane, octane, toluene, and xylene, and highly polar solvents such as water, methanol, ethanol, propanol, butanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, tetrahydrofuran, dioxane, and N,N-dimethylformamide can be used. These polymerization solvents can be used alone or in combination of two or more.
[0120] Furthermore, the polymerization temperature in the radical polymerization is preferably 0°C to 110°C from the viewpoint of polymerization rate.
[0121] The (meth)acrylic copolymer preferably has a structural unit derived from a monomer having an alkyl group with a carbon number of 6 or more. When the (meth)acrylic copolymer has a structural unit derived from a monomer having an alkyl group with a carbon number of 6 or more, the main body of the adhesive layer becomes softer, the viscosity of the adhesive solution is further reduced, and thus the processability is further improved.
[0122] The carbon number of the alkyl group having more than 6 carbon atoms in the monomer having an alkyl group having more than 6 carbon atoms is preferably 6 or more and 16 or less. By making the (meth)acrylic copolymer have a structural unit derived from a monomer having an alkyl group having more than 6 carbon atoms and less than 16 carbon atoms, the fluidity of the main body of the obtained adhesive layer is improved, and the adhesion of the adhesive layer to the rough surface becomes better. The carbon number of the alkyl group having more than 6 carbon atoms in the monomer having an alkyl group having more than 6 carbon atoms is more preferably 6 or more and less than 12. In addition, in the monomer having an alkyl group having more than 6 carbon atoms, the alkyl group having more than 6 carbon atoms may have a branched chain or may not have a branched chain, but preferably does not have a branched chain. By making the alkyl group of the monomer having more than 6 carbon atoms not have a branched chain, the storage modulus of the adhesive layer is low at low temperature to room temperature, and on the other hand, the storage modulus becomes high at high temperature, so that the heat resistance is better and the adhesion to the rough surface is better.
[0123] Examples of the monomer having an alkyl group having 6 or more carbon atoms include alkyl (meth)acrylates having an alkyl group having 6 or more carbon atoms.
[0124] Examples of the alkyl (meth)acrylate having an alkyl group with 6 or more carbon atoms include n-heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, cetyl (meth)acrylate, isostearyl acrylate, and eicosyl (meth)acrylate. These alkyl (meth)acrylates having an alkyl group with 6 or more carbon atoms may be used alone or in combination of two or more. Among them, n-heptyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred.
[0125] It should be noted that, in the present specification, the above-mentioned “(meth)acrylate” means acrylate or methacrylate.
[0126] The preferred lower limit of the content ratio of the structural unit of the monomer having an alkyl group with more than 6 carbon atoms in the above-mentioned (meth) acrylic copolymer is 50% by mass. By making the content ratio of the structural unit of the monomer having an alkyl group with more than 6 carbon atoms more than 50% by mass, the glass transition temperature of the above-mentioned (meth) acrylic copolymer becomes low, the fluidity of the main body in the obtained adhesive layer is improved, and the adhesion of the adhesive layer to the rough surface becomes more excellent. In addition, the main body of the adhesive layer becomes softer, and the viscosity of the adhesive solution is further reduced, so the processability is further improved. In addition, the compatibility with the tackifying resin described later is also improved. The more preferred lower limit of the content ratio of the structural unit of the monomer having an alkyl group with more than 6 carbon atoms is 60% by mass, and the further preferred lower limit is 70% by mass.
[0127] In addition, the preferred upper limit of the content ratio of the structural unit derived from the monomer having an alkyl group with more than 6 carbon atoms in the above-mentioned (meth) acrylic copolymer is 98% by mass. By making the content ratio of the structural unit derived from the monomer having an alkyl group with more than 6 carbon atoms less than 98% by mass, the glass transition temperature of the above-mentioned (meth) acrylic copolymer will not become too low, the cohesive force of the main body in the obtained adhesive layer becomes greater, and the heat resistance of the adhesive layer becomes better. The more preferred upper limit of the content ratio of the structural unit derived from the monomer having an alkyl group with more than 6 carbon atoms is 97% by mass, and the further preferred upper limit is 95% by mass.
[0128] The (meth)acrylic copolymer may have a structural unit derived from an alkyl (meth)acrylate having an alkyl group having 5 or less carbon atoms.
[0129] Examples of the alkyl (meth)acrylate having an alkyl group with a carbon number of 5 or less include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, and butyl (meth)acrylate. These alkyl (meth)acrylates having an alkyl group with a carbon number of 5 or less may be used alone or in combination of two or more. Among them, butyl (meth)acrylate is preferred.
[0130] The content ratio of the structural unit derived from the above-mentioned (meth) acrylic acid alkyl ester having an alkyl group with a carbon number of 5 or less is preferably 25% by mass or more and less than 50% by mass. By making the content ratio of the structural unit derived from the above-mentioned (meth) acrylic acid alkyl ester having an alkyl group with a carbon number of 5 or less 25% by mass or more, the glass transition temperature of the above-mentioned (meth) acrylic acid copolymer becomes sufficiently high, so the cohesive force of the main body in the obtained adhesive layer becomes greater, and the heat resistance of the adhesive layer becomes better. If the above-mentioned content ratio is less than 50% by mass, the glass transition temperature of the above-mentioned (meth) acrylic acid copolymer will not become too high, the fluidity of the main body in the obtained adhesive layer is improved, and the adhesion of the adhesive layer to the rough surface becomes better. The more preferred lower limit of the above-mentioned content ratio is 30% by mass, and the more preferred upper limit is 45% by mass.
[0131] The (meth) acrylic copolymer preferably has a structural unit derived from a monomer containing a crosslinkable functional group. By making the (meth) acrylic copolymer have the structural unit derived from a monomer containing a crosslinkable functional group, the (meth) acrylic copolymer and the tackifying resin described later construct a crosslinked structure with the help of a crosslinking agent described later, thereby increasing the cohesive force of the main body in the obtained adhesive layer and improving the heat resistance of the adhesive layer. Examples of the crosslinkable functional group include a hydroxyl group, a carboxyl group, a silyl group, a glycidyl group, an amino group, an amide group, a nitrile group, an alkoxy group, an acetoacetyl group, and the like. Among them, hydroxyl groups and carboxyl groups are preferred from the perspective of easily adjusting the cohesive force of the main body in the adhesive layer.
[0132] Examples of the crosslinkable functional group-containing monomer having a hydroxyl group as the crosslinkable functional group include 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, and hydroxypropyl (meth)acrylate.
[0133] Examples of the crosslinkable functional group-containing monomer having a carboxyl group as the crosslinkable functional group include (meth)acrylic acid, itaconic acid, maleic anhydride, crotonic acid, maleic acid, fumaric acid, etc. Among them, acrylic acid is preferred.
[0134] As a crosslinkable functional group-containing monomer which has a glycidyl group as the said crosslinkable functional group, glycidyl (meth)acrylate is mentioned, for example.
[0135] Examples of the crosslinkable functional group-containing monomer having an amide group as the crosslinkable functional group include hydroxyethylacrylamide, isopropylacrylamide, and dimethylaminopropylacrylamide.
[0136] Examples of the crosslinkable functional group-containing monomer having a nitrile group as the crosslinkable functional group include acrylonitrile and the like.
[0137] The preferred lower limit of the content ratio of the structural unit derived from the monomer containing crosslinkable functional groups in the above-mentioned (meth) acrylic copolymer is 0.05% by mass, and the preferred upper limit is 20% by mass. By making the content ratio of the structural unit derived from the monomer containing crosslinkable functional groups to be 0.05% by mass or more, the cohesive force of the main body in the obtained adhesive layer becomes greater, and the heat resistance of the adhesive layer becomes better. By making the content ratio of the structural unit derived from the monomer containing crosslinkable functional groups to be 20% by mass or less, the fluidity of the main body in the obtained adhesive layer is improved, and the adhesion of the adhesive layer to the rough surface becomes better. The more preferred lower limit of the content ratio of the structural unit derived from the monomer containing crosslinkable functional groups is 0.1% by mass, and the more preferred upper limit is 15% by mass.
[0138] In the case where the (meth) acrylic copolymer has a structural unit derived from a monomer containing a crosslinkable functional group having a hydroxyl group as the crosslinkable functional group, the preferred lower limit of the content ratio of the structural unit derived from the monomer containing a crosslinkable functional group is 0.03% by mass, and the preferred upper limit is 1% by mass. By making the content ratio of the structural unit derived from the monomer containing a crosslinkable functional group having a hydroxyl group as the crosslinkable functional group greater than 0.03% by mass, the cohesive force of the main body in the obtained adhesive layer becomes greater, and the heat resistance of the adhesive layer becomes better. By making the content ratio of the structural unit derived from the monomer containing a crosslinkable functional group having a hydroxyl group as the crosslinkable functional group less than 1% by mass, the gel fraction of the obtained adhesive layer does not become too high, and the adhesiveness of the adhesive layer to the rough surface becomes better. The more preferred lower limit of the content ratio of the structural unit derived from the crosslinkable functional group-containing monomer having a hydroxyl group as the above-mentioned crosslinkable functional group is 0.05% by mass, the further preferred lower limit is 0.06% by mass, the more preferred upper limit is 0.5% by mass, the further preferred upper limit is 0.3% by mass, and the particularly preferred upper limit is 0.1% by mass.
[0139] In addition, when the (meth) acrylic copolymer has a structural unit derived from a monomer containing a crosslinkable functional group having a carboxyl group as the crosslinkable functional group, the preferred lower limit of the content ratio of the structural unit derived from the monomer containing a crosslinkable functional group is 2% by mass, and the preferred upper limit is 15% by mass. By making the content ratio of the structural unit derived from the monomer containing a crosslinkable functional group having a carboxyl group as the crosslinkable functional group more than 2% by mass, the gel fraction of the obtained adhesive layer is easily increased, and the glass transition temperature of the (meth) acrylic copolymer is sufficiently increased, so that the cohesive force of the main body in the obtained adhesive layer becomes greater. As a result, the heat resistance of the adhesive layer becomes better. By making the content ratio of the structural unit derived from the monomer containing a crosslinkable functional group having a carboxyl group as the crosslinkable functional group less than 15% by mass, the glass transition temperature of the (meth) acrylic copolymer does not become too high, and the adhesiveness of the adhesive layer to the rough surface becomes better. The more preferred lower limit of the content of the structural unit derived from the crosslinkable functional group-containing monomer having a carboxyl group as the crosslinkable functional group is 3% by mass, and a further preferred lower limit is 5% by mass. The more preferred upper limit is 10% by mass, and a further preferred upper limit is 8% by mass.
[0140] The (meth)acrylic copolymer may contain, as necessary, a structural unit derived from the monomer having an alkyl group with 6 or more carbon atoms, a structural unit derived from the (meth)acrylic acid alkyl ester having an alkyl group with 5 or less carbon atoms, and a structural unit derived from another copolymerizable polymerizable monomer other than the structural unit derived from the monomer having a crosslinkable functional group.
[0141] The above-mentioned adhesive contains a cross-linking agent.
[0142] As the crosslinking agent, for example, isocyanate crosslinking agents, aziridine crosslinking agents, epoxy crosslinking agents, metal chelate crosslinking agents, etc. can be selected and used according to the type of the crosslinking functional group of the (meth)acrylic copolymer. Among them, isocyanate crosslinking agents are preferred from the perspective of being able to selectively crosslink hydroxyl groups and carboxyl groups and being easy to control the crosslinking structure. It is particularly preferred that 80 parts by mass or more of an isocyanate crosslinking agent having two or more isocyanate groups in one molecule is contained in 100 parts by mass of the crosslinking agent.
[0143] Examples of commercially available products of the isocyanate crosslinking agent include CORONATE HX and CORONATE L (both manufactured by Tosoh Corporation) and MYTEX NY260A (manufactured by Mitsubishi Chemical Co., Ltd.).
[0144] The crosslinking agent preferably has a polyvalent functional group number because the crosslinked structure can be easily increased in dimension and networked, and the resulting pressure-sensitive adhesive layer can have a greater cohesive force in the bulk.
[0145] The above adhesive contains a tackifying resin.
[0146] When the pressure-sensitive adhesive contains the tackifier resin, the resulting pressure-sensitive adhesive layer has excellent adhesion to an adherend.
[0147] The preferred lower limit of the softening temperature of the tackifier resin is 90°C, and the preferred upper limit is 180°C. By setting the softening temperature of the tackifier resin to 90°C or higher, the heat resistance of the adhesive layer becomes better, and the creep resistance at high temperature is further improved. By setting the softening temperature of the tackifier resin to 180°C or lower, the adhesive layer becomes softer and the adhesion to the rough surface becomes better. The more preferred lower limit of the softening temperature of the tackifier resin is 100°C, the further preferred lower limit is 110°C, the particularly preferred lower limit is 120°C, the more preferred upper limit is 170°C, and the further preferred upper limit is 165°C.
[0148] In addition, the said "softening temperature" means the softening temperature measured by the JIS K2207 ring and ball method.
[0149] The preferred lower limit of the hydroxyl value of the above-mentioned tackifying resin is 10 mgKOH / g, and the preferred upper limit is 200 mgKOH / g. By making the hydroxyl value of the above-mentioned tackifying resin above 10 mgKOH / g, the softening temperature of the above-mentioned tackifying resin is easily increased. By making the hydroxyl value of the above-mentioned tackifying resin below 200 mgKOH / g, the reactivity with the above-mentioned cross-linking agent will not become too high, and the situation of hindering the crosslinking of the above-mentioned (meth) acrylic copolymer or the grafting reaction with the (meth) acrylic copolymer can be suppressed. The more preferred lower limit of the hydroxyl value of the above-mentioned tackifying resin is 20 mgKOH / g, the further preferred lower limit is 25 mgKOH / g, the particularly preferred lower limit is 30 mgKOH / g, the more preferred upper limit is 150 mgKOH / g, the further preferred upper limit is 120 mgKOH / g, and the particularly preferred upper limit is 100 mgKOH / g.
[0150] In addition, the said "hydroxyl value" can be measured by JIS K1557 (phthalic anhydride method).
[0151] Examples of the tackifier resin include rosin-based resins such as rosin ester-based resins, terpene-based resins such as terpene phenol resins, and petroleum-based resins. These tackifier resins may be used alone or in combination of two or more.
[0152] Among them, rosin ester resins, terpene phenol resins, and combinations thereof are preferred, and terpene phenol resins are more preferred.
[0153] The terpene-phenol resin is a resin obtained by polymerizing terpene in the presence of phenol. The terpene-phenol resin has good compatibility with the (meth)acrylic copolymer, and is easily grafted with the (meth)acrylic copolymer, and easily enters the interior of the adhesive layer. Therefore, the surface of the adhesive layer is rich in polymer (Japanese: ポリマーリッチ) and becomes soft, and can have higher adhesion to rough surfaces. On the other hand, by grafting the terpene-phenol resin with the (meth)acrylic copolymer, the cohesive force of the main body of the adhesive layer is further improved, so the creep resistance of the adhesive layer becomes more excellent.
[0154] Examples of commercially available products of the terpene resins include YS Polyster G150 (hydroxyl value 140 mgKOH / g, softening temperature 150°C), YS Polyster T100 (hydroxyl value 60 mgKOH / g, softening temperature 100°C), YS Polyster G125 (hydroxyl value 140 mgKOH / g, softening temperature 125°C), YS Polyster T115 (hydroxyl value 60 mgKOH / g, softening temperature 115°C), YS Polyster T130 (hydroxyl value 60 mgKOH / g, softening temperature 130°C), and YS Polyster T160 (hydroxyl value 60 mgKOH / g, softening temperature 160°C) (all manufactured by Yasuhara Chemical Co., Ltd.).
[0155] The above-mentioned rosin ester resin refers to a resin obtained by esterifying a rosin resin, a disproportionated rosin resin, a hydrogenated rosin resin, a dimer of a resin acid such as a rosin acid (polymerized rosin resin), etc., which has a rosin acid as the main component, with an alcohol. The hydroxyl value is adjusted to the above-mentioned range by making a part of the hydroxyl groups of the alcohol used for esterification not be used for esterification but be contained in the resin. Examples of the alcohol include polyols such as ethylene glycol, glycerol, and pentaerythritol.
[0156] It should be noted that a resin obtained by esterifying a rosin resin is a rosin ester resin, a resin obtained by esterifying a disproportionated rosin resin is a disproportionated rosin ester resin, a resin obtained by esterifying a hydrogenated rosin resin is a hydrogenated rosin ester resin, and a resin obtained by esterifying a polymerized rosin resin is a polymerized rosin ester resin.
[0157] Examples of commercially available products of the disproportionated rosin ester resins include Super Ester A75 (hydroxyl value: 23 mgKOH / g, softening temperature: 75°C), Super Ester A100 (hydroxyl value: 16 mgKOH / g, softening temperature: 100°C), Super Ester A115 (hydroxyl value: 19 mgKOH / g, softening temperature: 115°C), and Super Ester A125 (hydroxyl value: 15 mgKOH / g, softening temperature: 125°C) (all manufactured by Arakawa Chemical Industries, Ltd.).
[0158] Examples of the hydrogenated rosin ester resin include Pinecrystal KE-359 (hydroxyl value: 42 mgKOH / g, softening temperature: 100° C.) and Ester Gum H (hydroxyl value: 29 mgKOH / g, softening temperature: 70° C.) (both manufactured by Arakawa Chemical Industries, Ltd.).
[0159] Examples of the polymerized rosin ester resin include PENSEL D135 (hydroxyl value: 45 mgKOH / g, softening temperature: 135° C.), PENSEL D125 (hydroxyl value: 34 mgKOH / g, softening temperature: 125° C.), and PENSEL D160 (hydroxyl value: 42 mgKOH / g, softening temperature: 160° C.) (all manufactured by Arakawa Chemical Industries, Ltd.).
[0160] The preferred lower limit of the content of the tackifier resin is 10 parts by mass, and the preferred upper limit is 60 parts by mass relative to 100 parts by mass of the (meth) acrylic copolymer. By making the content of the tackifier resin within the above range, the adhesion of the interface of the adhesive layer becomes more excellent, and the retention performance becomes more excellent. The more preferred lower limit of the content is 15 parts by mass, the further preferred lower limit is 20 parts by mass, the more preferred upper limit is 50 parts by mass, and the further preferred upper limit is 45 parts by mass.
[0161] The adhesive may contain additives such as solvents, plasticizers, emulsifiers, softeners, fillers, pigments, dyes, silane coupling agents, antioxidants, etc. as needed. In the adhesive tape of the present invention, the amount of the solvent that is the source of CO2 discharged during the manufacturing process can be reduced.
[0162] The above-mentioned adhesive preferably contains 0.03% or more of a compound having a hydroxyl group in the solid content, and contains 2% or more of a compound having a carboxyl group in the solid content. By making the above-mentioned adhesive contain 0.03% or more of a compound having a hydroxyl group in the solid content, and containing 2% or more of a compound having a carboxyl group in the solid content, the cohesive force of the body in the obtained adhesive layer becomes greater, and the heat resistance of the above-mentioned adhesive layer becomes more excellent. The above-mentioned adhesive more preferably contains 0.05% or more of the above-mentioned compound having a hydroxyl group. In addition, the above-mentioned adhesive more preferably contains 3% or more of the above-mentioned compound having a carboxyl group.
[0163] In addition, the compound having a hydroxyl group and the compound having a carboxyl group may be any component contained in the solid content of the binder.
[0164] It should be noted that the above-mentioned "solid content" refers to components other than the solvent.
[0165] The upper limit of the viscosity of the adhesive when applied is preferably 10,000 mPa·s. By setting the viscosity of the adhesive to 10,000 mPa·s or less, it is easy to apply the adhesive smoothly without causing problems such as bubbles and glue lines. The upper limit of the viscosity of the adhesive when applied is more preferably 9000 mPa·s, and the upper limit is still more preferably 8000 mPa·s.
[0166] In addition, the preferred lower limit of the viscosity when applying the above-mentioned adhesive is 1500mPa·s. By setting the viscosity when applying the above-mentioned adhesive to be 1500mPa·s or more, the pressure when squeezing out the adhesive can be sufficiently obtained, and the adhesive can be easily applied to the target thickness and width. The more preferred lower limit of the viscosity when applying the above-mentioned adhesive is 2000mPa·s.
[0167] The viscosity of the adhesive when applied can be measured using a B-type viscometer under the conditions of 23° C. and 12 rpm.
[0168] The preferred lower limit of the glass transition temperature of the above-mentioned adhesive layer is -10°C, and the preferred upper limit is 30°C. By setting the glass transition temperature of the above-mentioned adhesive layer to be above -10°C, the heat resistance becomes higher and the cohesive force of the body also becomes higher, so the retention performance and high-temperature resilience resistance become better. By setting the glass transition temperature of the above-mentioned adhesive layer to be below 30°C, the adhesion to the interface becomes better. The more preferred lower limit of the glass transition temperature of the above-mentioned adhesive layer is -5°C, the further preferred lower limit is 0°C, the further preferred lower limit is 5°C, the more preferred upper limit is 25°C, the further preferred upper limit is 20°C, and the further preferred upper limit is 15°C.
[0169] In addition, in this specification, the said "glass transition temperature" means the temperature at which the maximum value of the loss tangent (tan δ) obtained by dynamic viscoelasticity measurement appears due to the micro-Brownian motion.
[0170] As the dynamic viscoelasticity measurement performed in the measurement of the glass transition temperature of the pressure-sensitive adhesive layer and the storage elastic modulus described later, for example, the following method can be employed.
[0171] That is, first, the samples of the adhesive layers were overlapped to prepare a laminate with a thickness of about 1 mm, and the laminate was cut into 6 mm×10 mm to obtain a test piece. The obtained test piece was subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (IT Measurement and Control Co., Ltd., "DVA-200") in a shear mode in a nitrogen atmosphere, at a measuring temperature of -40°C to 140°C, a heating rate of 5°C / min, a frequency of 10 Hz, and a strain of 0.08%.
[0172] The preferred lower limit of the storage modulus G' (80°C) of the adhesive layer at 80°C is 1.0×10 4 Pa. By making the storage modulus G' (80°C) of the above-mentioned adhesive layer 1.0×10 4 Pa or more, the cohesive force of the adhesive layer at high temperature becomes greater, and the creep resistance and high temperature rebound resistance at high temperature become better. The more preferred lower limit of the storage modulus G' (80°C) of the adhesive layer is 1.5×10 4 Pa, and a further preferred lower limit is 2.0×10 4 Pa, and a further preferred lower limit is 5.0×10 4 Pa, the lower limit of which is particularly preferred is 8.0×10 4 Pa.
[0173] If the storage modulus G' (80°C) of the adhesive layer is too high, the storage modulus at room temperature will also increase, and the adhesive force to the rough surface will decrease. Therefore, the upper limit of the storage modulus G' (80°C) of the adhesive layer is preferably 2.0×10 5 Pa.
[0174] The preferred lower limit of the thickness of the above-mentioned adhesive layer is 10μm, and the preferred upper limit is 100μm. By making the thickness of the above-mentioned adhesive layer more than 10μm, the penetration of the above-mentioned adhesive layer into the adherend is increased, and the peeling resistance becomes larger, so the adhesion to the rough surface becomes better. By making the above-mentioned thickness less than 100μm, the offset amount when the shear force is applied to the above-mentioned adhesive layer is reduced, so the retention performance of the above-mentioned adhesive layer becomes better. The more preferred lower limit of the thickness of the above-mentioned adhesive layer is 12μm, the further preferred lower limit is 15μm, the more preferred upper limit is 60μm, and the further preferred upper limit is 50μm.
[0175] The pressure-sensitive adhesive tape preferably has a substrate.
[0176] As the substrate, a resin film is preferred.
[0177] The resin film is preferably a polyester resin film or a polypropylene resin film. Among them, a polyester resin film is preferred from the viewpoints of flatness, small thickness variation, and high strength. Among polyester resin films, a polyethylene terephthalate film is more preferred.
[0178] The above-mentioned base material may contain additives such as a filler, an ultraviolet absorber, a light stabilizer, and an antistatic agent within a range that does not impair the physical properties thereof.
[0179] The thickness of the substrate is appropriately selected according to the application, and the preferred lower limit is 5 μm, and the preferred upper limit is 200 μm. By making the thickness of the substrate below 200 μm, it becomes a substrate suitable for use in fixed applications of electronic components, and can reduce CO2 emissions during manufacturing. The more preferred lower limit of the thickness of the substrate is 10 μm, the further preferred lower limit is 15 μm, the more preferred upper limit is 100 μm, and the further preferred upper limit is 50 μm.
[0180] The pressure-sensitive adhesive tape of the present invention may have the pressure-sensitive adhesive layer on only one side of the substrate or on both sides of the substrate, but preferably has the pressure-sensitive adhesive layer on both sides of the substrate.
[0181] The method for producing the pressure-sensitive adhesive tape of the present invention is not particularly limited. For example, when pressure-sensitive adhesive layers having the same composition and thickness are provided on both sides of the substrate, the following method can be mentioned.
[0182] First, an adhesive comprising a (meth) acrylic copolymer, a crosslinking agent, a tackifying resin and a solvent, and other components used as needed is prepared. Next, the above-obtained adhesive is applied to the release-treated surface of a release film through release treatment and dried to prepare a laminated sheet having an adhesive layer on the release-treated surface of the release film. Two laminated sheets are prepared in the same manner. Next, the adhesive layers of the two laminated sheets are transferred to a substrate and laminated and integrated to obtain an adhesive sheet having an adhesive layer on both sides of the substrate.
[0183] From the viewpoint of improving both the holding performance and the adhesiveness of the pressure-sensitive adhesive tape of the present invention, the pressure-sensitive adhesive tape of the present invention preferably has excellent high-temperature repulsion resistance.
[0184] It should be noted that the high temperature repulsion resistance can be evaluated, for example, by the following method. Figure 2 Schematic diagram showing the method of the high-temperature repulsion resistance test is shown in FIG.
[0185] That is, the adhesive tape 1 of the present invention is cut into a strip of 25 mm width × 300 mm length, and the adhesive layer on the side not to be measured is bonded to a PET film 4 (thickness 100 μm, 25 mm width, length 300 mm). Next, the adhesive layer on the side to be measured is bonded to a SUS plate 2 (SUS304 plate washed with ethanol and dried) in a manner that the short side of the adhesive tape 1 overlaps one side of the SUS plate, and a 2 kg rubber roller is reciprocated 5 times at a speed of 300 mm / min to perform pressure bonding, and then the test piece is left to stand at 23°C for 72 hours to prepare a test piece. The prepared test piece is further placed in an oven at 80°C for heating for 15 minutes, and then a high temperature rebound resistance test is performed in which the following state is maintained for 144 hours, wherein a 100 g weight 5 is used to apply a load of 100 g to the front end of the test piece in a perpendicular direction to the test piece under the condition of 80°C. When the entire adhesive tape fell, the falling time was measured with the time for which a load of 100 g was applied as 0 hours. When the entire adhesive tape did not fall, the peeling length of the adhesive tape was measured by visual observation ( Figure 2 The result of the high-temperature repulsion resistance test showed that the adhesive tape of the present invention was excellent in high-temperature repulsion resistance when the entire adhesive tape did not fall off and the peeling length was 60 mm or less.
[0186] Effects of the Invention
[0187] According to the present invention, it is possible to provide a pressure-sensitive adhesive tape including a pressure-sensitive adhesive layer that uses a (meth)acrylic copolymer having a low molecular weight and has excellent holding performance and adhesiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0188] Figure 1 It is a schematic diagram showing the method of the holding test.
[0189] Figure 2 It is a schematic diagram showing the method of the high temperature repulsion resistance test. DETAILED DESCRIPTION
[0190] Hereinafter, the embodiment of the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0191] (Preparation of acrylic copolymers A to S)
[0192] The solvent shown in Table 1 was added to a reactor equipped with a thermometer, a stirrer, and a condenser, and after nitrogen substitution, the reactor was heated and refluxed. After the solvent boiled, the polymerization initiator 1 shown in Table 1 was added, and then the mixed solution of the monomers and the chain transfer agent shown in Table 1 was dripped into the reactor from the dropping funnel over 2 hours. Then, the polymerization initiator 2 shown in Table 1 was further added, and the time of starting dripping was set as the polymerization start time. The polymerization reaction was carried out for a total of 6 hours from the start of polymerization to obtain a solution containing acrylic copolymers A to S.
[0193] It should be noted that the materials in Table 1 are as follows.
[0194] BA: Butyl acrylate
[0195] 2EHA: 2-Ethylhexyl acrylate
[0196] C7: n-heptyl acrylate
[0197] HEA: Hydroxyethyl acrylate
[0198] Aac: Acrylic
[0199] AIBN: 2,2'-azobis(isobutyronitrile)
[0200] [Table 1]
[0201]
[0202] (Examples 1 to 23, Comparative Examples 1 to 8)
[0203] (1) Preparation of adhesive
[0204] To the obtained solution containing acrylic copolymers A to S, various materials were added in the compositions shown in Tables 2 and 3, and stirred to obtain an adhesive. The content ratio of the compound having a hydroxyl group in the solid content and the content ratio of the compound having a carboxyl group in the solid content of the obtained adhesive are shown in Tables 2 and 3.
[0205] It should be noted that the materials in Table 2 and Table 3 are as follows.
[0206] CORONATE L45: Isocyanate crosslinking agent (manufactured by Tosoh Corporation)
[0207] KE388: Hydrogenated rosin ester resin (produced by Arakawa Chemical Industries, Ltd., hydroxyl value 45 mgKOH / g, softening temperature 150°C)
[0208] KE359: Hydrogenated rosin ester resin (produced by Arakawa Chemical Industries, Ltd., hydroxyl value 40 mgKOH / g, softening temperature 100°C)
[0209] D135: Polymerized rosin ester resin (produced by Arakawa Chemical Industries, Ltd., hydroxyl value 40 mgKOH / g, softening temperature 135°C)
[0210] G150: Terpene resin (manufactured by Yasuhara Chemical Co., Ltd., hydroxyl value 100 mgKOH / g, softening temperature 150°C)
[0211] (2) Production of adhesive tape
[0212] A polyethylene terephthalate film having one side subjected to a release treatment was prepared. The adhesive obtained in the above "(1) Preparation of Adhesive" was applied to the release-treated surface of the polyethylene terephthalate film, and dried at 110° C. for 5 minutes to crosslink the (meth)acrylic copolymer in the adhesive, thereby preparing a laminated sheet having an adhesive layer on the release-treated surface of the polyethylene terephthalate film. Another laminated sheet was prepared in the same manner, and a total of two laminated sheets were obtained.
[0213] Next, a polyethylene terephthalate film (thickness 25 μm) was prepared as a substrate. On the surface of one side of the substrate, a laminated sheet was laminated from the adhesive layer, and the adhesive layer was transferred and laminated to the substrate. On the surface of the other side of the substrate, another laminated sheet was laminated from the adhesive layer, and the adhesive layer was transferred and laminated to the substrate. Thus, a double-sided adhesive tape having adhesive layers having thicknesses shown in Tables 2 and 3 on both sides of the substrate was obtained.
[0214] (Weight Average Molecular Weight (Mw copolymer), Peak Top Molecular Weight (Mp copolymer), and Polydispersity Index (Mw copolymer / Mn copolymer) of (meth)acrylic Copolymer Obtained by Alkali Decomposition)
[0215] 300 mg of the adhesive layer was collected from the obtained double-sided adhesive tape. The collected adhesive layer, 6 mL of ethanol, and 7 mL of a 60% KOH aqueous solution were added to a pressure vessel, and pressure hydrolysis was performed in an oven at 160° C. for 60 hours, thereby alkali decomposing the crosslinking points of the crosslinked product in the adhesive layer to obtain a (meth)acrylic acid copolymer.
[0216] The obtained (meth)acrylic acid-based copolymer was analyzed by gel permeation chromatography (GPC) (manufactured by Waters, "2690 Separations Model") to measure the molecular weight distribution based on polystyrene conversion. The weight average molecular weight (Mw copolymer), peak top molecular weight (Mp copolymer) and polydispersity coefficient (Mw copolymer / Mn copolymer) of the (meth)acrylic acid-based copolymer obtained by alkali decomposition derived from the obtained molecular weight distribution are shown in Tables 2 and 3. The above GPC was performed under the following conditions.
[0217] Eluent: Tetrahydrofuran (THF)
[0218] Flow rate: 0.4mL / min
[0219] Detector: Differential Refractometer RI
[0220] Column: LF-804 (manufactured by SHOKO)
[0221] Column temperature (measurement temperature): 40°C
[0222] Injection volume: 20 μL
[0223] (Weight Average Molecular Weight of Sol Component (Mwsol) and Mwsol-Mwcopolymer)
[0224] The obtained pressure-sensitive adhesive layer of the double-sided pressure-sensitive adhesive tape was immersed in tetrahydrofuran (THF) at 23° C. for 24 hours, and the insoluble components were removed by filtration using a 200-mesh metal mesh to obtain a sol component of the pressure-sensitive adhesive layer.
[0225] The sol component of the obtained adhesive layer was analyzed by gel permeation chromatography (GPC) (manufactured by Waters, "2690 Separations Model") to measure the molecular weight distribution based on polystyrene conversion. The weight average molecular weight of the sol component derived from the obtained molecular weight distribution (Mw sol) and the value obtained by subtracting the weight average molecular weight of the (meth)acrylic copolymer obtained by alkali decomposition from the weight average molecular weight of the sol component (Mw sol - Mw copolymer) are shown in Tables 2 and 3. The above GPC was performed under the following conditions.
[0226] Eluent: Tetrahydrofuran (THF)
[0227] Flow rate: 0.4mL / min
[0228] Detector: Differential Refractometer RI
[0229] Column: LF-804 (manufactured by SHOKO)
[0230] Column temperature (measurement temperature): 40°C
[0231] Injection volume: 20 μL
[0232] (Gel fraction of adhesive layer)
[0233] The adhesive layer W1 (g) of the obtained double-sided adhesive tape was collected, and the collected adhesive layer was immersed in ethyl acetate at 23°C for 24 hours, and the insoluble components were filtered out with a 200-mesh metal mesh. The residue on the metal mesh was heated and dried at 110°C, and the mass W2 (g) of the obtained dry residue was measured. Based on the obtained W1 and W2, the gel fraction (crosslinking degree) was calculated by the following formula (I). The obtained gel fractions are shown in Tables 2 and 3.
[0234] Gel fraction (mass %) = 100 × W2 / W1 (I)
[0235] (Storage modulus G' (80°C) and glass transition temperature of adhesive layer)
[0236] The adhesive layers of the obtained double-sided adhesive tape were overlapped to make a laminate with a thickness of about 1 mm, and the test piece was cut into 6 mm × 10 mm. For the obtained test piece, a dynamic viscoelasticity measurement device (IT Measurement and Control Co., Ltd., "DVA-200") was used to measure the dynamic viscoelasticity under the conditions of -40°C to 140°C, a heating rate of 5°C / min, a frequency of 10 Hz, and a strain of 0.08% in a nitrogen atmosphere using a shear mode, and the storage modulus G' (80°C) at 80°C was obtained. In addition, the temperature at which the maximum value caused by micro-Brownian motion appears in the maximum value of the loss tangent (tanδ) obtained by the dynamic viscoelasticity measurement is taken as the glass transition temperature. The obtained storage modulus G' (80°C) and glass transition temperature are shown in Tables 2 and 3.
[0237] [Table 2]
[0238]
[0239] [Table 3]
[0240]
[0241] <Evaluation>
[0242] The pressure-sensitive adhesives and double-sided pressure-sensitive adhesive tapes obtained in Examples and Comparative Examples were evaluated as follows.
[0243] (Processability)
[0244] The solid content concentration of the obtained adhesive was adjusted to 60% by mass, and the viscosity was measured at 23°C and 12 rpm using a B-type viscometer ("RVDV-2+PRO" manufactured by Eikon Seiki Co., Ltd.) and SPINDLE S04. In addition, the viscosity of the adhesive adjusted to 70% by mass was similarly measured, and the case where the obtained viscosity was 10,000 mPa·s or less was marked as "○", and the case where it exceeded 10,000 mPa·s was marked as "×", and the processability was evaluated.
[0245] (Maintain performance)
[0246] The obtained double-sided adhesive tape was cut into strips with a width of 25 mm and then bonded to a SUS plate (SUS304 plate washed with ethanol and wiped dry) by moving a 2 kg rubber roller back and forth once at a speed of 300 mm / min. Next, a dent was introduced into the adhesive tape so that the bonding area became 25 mm×25 mm. Then, after standing at 23°C for 20 minutes, it was placed in an oven at 80°C and heated for 15 minutes. Then, while being maintained at 80°C, the adhesive tape was heated as follows. Figure 1 As shown, a load of 1 kg was applied in the shear direction using a 1 kg weight 3. It was confirmed whether the adhesive tape had fallen off, and if it had not fallen off after 24 hours, the displacement (deviation) from the dent position was measured using a ruler magnifier.
[0247] The holding performance was evaluated by rating “○” when the adhesive tape did not fall off and the displacement was 1 mm or less, rating “△” when the adhesive tape did not fall off and the displacement exceeded 1 mm, and rating “×” when the adhesive tape fell off.
[0248] (Adhesion)
[0249] After the adhesive tape was cut into a strip with a width of 25 mm, it was bonded to a SUS plate (SUS304 plate wiped dry after cleaning with ethanol) by reciprocating a 2 kg rubber roller once at a speed of 300 mm / min. Next, it was left to stand for 20 minutes at a temperature of 23°C and a relative humidity of 50%, thereby obtaining a test piece. For the obtained test piece, a tensile test was performed using a tensile testing machine (manufactured by A&D, "RTI-1310"), according to JIS Z0237, at 23°C, a peeling speed of 300 mm / min, and a peeling angle of 180°, and the 180° peeling adhesive force was measured.
[0250] The adhesiveness was evaluated by evaluating the 180° peel strength of 18 N / 25 mm or more as “○”, 15 N / 25 mm or more and less than 18 N / 25 mm as “△”, and less than 15 N / 25 mm as “×”.
[0251] In addition, a rough surface SUS plate was used instead of the SUS plate (SUS304 plate cleaned with ethanol and wiped dry), and the 180° peeling adhesive strength was measured in the same manner. The rough surface SUS plate was obtained by grinding the SUS304 plate cleaned with ethanol and wiped dry with a grinding paper with a grain size of 80. In addition, the surface of the rough surface SUS plate was observed using a laser microscope, and the results showed that Ra was 1.7μm and Rz was 10μm.
[0252] [Table 4]
[0253]
[0254]
[0255] Industrial Applicability
[0256] According to the present invention, it is possible to provide a pressure-sensitive adhesive tape including a pressure-sensitive adhesive layer that uses a (meth)acrylic copolymer having a low molecular weight and has excellent holding performance and adhesiveness.
[0257] Description of Reference Numerals
[0258] 1: Adhesive tape
[0259] 2: SUS board
[0260] 3: 1kg load (heavy object)
[0261] 4: PET film
[0262] 5: 100g load (heavy object)
Claims
1. An adhesive tape, characterized in that: It has an adhesive layer, The adhesive layer contains a cross-linked product of an adhesive, wherein the adhesive comprises a (meth)acrylic copolymer, a cross-linking agent and a tackifying resin. When a (meth)acrylic acid-based copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is subjected to GPC measurement using a differential refractometer RI detection, the weight average molecular weight of the (meth)acrylic acid-based copolymer in the molecular weight range of 5,000 or more is 80,000 or more and less than 500,000, In a holding test in which a load of 1 kg is applied to the adhesive tape bonded to a SUS plate in a shear direction at 80° C. for 24 hours, the adhesive tape does not fall off, and The 180° peeling strength of the adhesive tape to the SUS plate was 15 N / 25 mm or more.
2. An adhesive tape, characterized in that: It has an adhesive layer, The adhesive layer contains a cross-linked product of an adhesive, wherein the adhesive comprises a (meth)acrylic copolymer, a cross-linking agent and a tackifying resin. When a (meth)acrylic acid-based copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is subjected to GPC measurement based on RI detection of a differential refractometer, the weight average molecular weight of the (meth)acrylic acid-based copolymer in the molecular weight range of 5,000 or more is 80,000 or more and less than 500,000, and The adhesive layer satisfies the following first constitution, the following second constitution, or the following third constitution, A first configuration: the adhesive contains 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the adhesive layer is 5% by mass or more; A second configuration: the adhesive comprises 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic acid-based copolymer, the gel fraction of the adhesive layer is less than 5% by mass, and a value obtained by subtracting a weight average molecular weight of the (meth)acrylic acid-based copolymer in a molecular weight range of 5,000 or more when subjected to GPC measurement using a differential refractometer RI detection on a sol component of the adhesive layer and obtained by alkali decomposition of the crosslinking points of the crosslinked product from a weight average molecular weight of the sol component in a molecular weight range of 5,000 or more when subjected to GPC measurement using a differential refractometer RI detection is 80,000 or more; A third configuration: the pressure-sensitive adhesive contains 0.1 parts by mass or more and less than 6 parts by mass of the cross-linking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction exceeding 30% by mass.
3. The adhesive tape according to claim 2, wherein The adhesive layer satisfies the first configuration.
4. The adhesive tape according to claim 2, wherein The adhesive layer satisfies the second configuration.
5. The adhesive tape according to claim 2, wherein The adhesive layer satisfies the third configuration.
6. The adhesive tape according to claim 1, wherein The adhesive layer satisfies the following first constitution, the following second constitution, or the following third constitution, A first configuration: the adhesive contains 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the adhesive layer is 5% by mass or more; A second configuration: the adhesive comprises 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic acid-based copolymer, the gel fraction of the adhesive layer is less than 5% by mass, and a value obtained by subtracting a weight average molecular weight of the (meth)acrylic acid-based copolymer in a molecular weight range of 5,000 or more when subjected to GPC measurement using a differential refractometer RI detection on a sol component of the adhesive layer and obtained by alkali decomposition of the crosslinking points of the crosslinked product from a weight average molecular weight of the sol component in a molecular weight range of 5,000 or more when subjected to GPC measurement using a differential refractometer RI detection is 80,000 or more; A third configuration: the pressure-sensitive adhesive contains 0.1 parts by mass or more and less than 6 parts by mass of the cross-linking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction exceeding 30% by mass.
7. The adhesive tape according to claim 2 or 6, wherein The adhesive layer has the following structure as the first structure: the adhesive contains 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the adhesive layer is 5% by mass or more and less than 30% by mass; or The adhesive layer has the following configuration as the third configuration: the adhesive contains 1.5 parts by mass or more and less than 6 parts by mass of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the adhesive layer has a gel fraction exceeding 30% by mass.
8. The adhesive tape according to claim 7, wherein The adhesive layer has the following configuration as the first configuration: the adhesive contains 6 parts by mass or more of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the adhesive layer has a gel fraction of 5% by mass or more and less than 30% by mass.
9. The adhesive tape according to claim 7, wherein The adhesive layer has the following configuration as the third configuration: the adhesive contains 1.5 parts by mass or more and less than 6 parts by mass of the crosslinking agent based on 100 parts by mass of the (meth)acrylic copolymer, and the adhesive layer has a gel fraction exceeding 30% by mass.
10. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8 or 9, wherein When the sol component of the pressure-sensitive adhesive layer is subjected to GPC measurement using a differential refractometer RI detection, the weight average molecular weight of the sol component in the molecular weight range of 5,000 or more is 50,000 or more and 500,000 or less.
11. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, wherein When a (meth)acrylic acid-based copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is subjected to GPC measurement using a differential refractometer RI detection, the peak top molecular weight of the (meth)acrylic acid-based copolymer in the molecular weight range of 5,000 or more is 70,000 or more and 300,000 or less.
12. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or 11, wherein The binder contains 0.03% by mass or more of a compound having a hydroxyl group in a solid content, and contains 2% by mass or more of a compound having a carboxyl group in a solid content.
13. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, wherein The (meth)acrylic copolymer includes 50% by mass or more of a structural unit derived from a monomer having an alkyl group having 6 or more carbon atoms.
14. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, wherein The adhesive layer has a glass transition temperature of -10°C to 30°C.
15. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14, wherein The storage modulus G' (80°C) of the adhesive layer at 80°C is 1.0×10 4 Pa or above.
16. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, wherein The adhesive layer has a thickness of 10 μm or more and 100 μm or less.
17. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16, wherein The pressure-sensitive adhesive tape has a substrate, the substrate is a polyester resin film or a polypropylene resin film, and the thickness of the substrate is 5 μm or more and 200 μm or less.
18. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17, wherein The pressure-sensitive adhesive tape includes a substrate and has the pressure-sensitive adhesive layers on both sides of the substrate.
Citation Information
Patent Citations
Impact-absorbing tape
JP2009242541A
Pressure-sensitive adhesive sheet for front plate of display device
JP2009258274A
Tacky adhesive and tacky adhesive sheet
JP2012214544A